Using Stress-Based Animal Models to Understand the Mechanisms Underlying Psychiatric and Somatic Disorders - Stefan O. Reber (Frontiers Research Topics, 2017)
Chronic or repeated stress, particularly psychosocial stress, is an acknowledged risk factor for numerous affective and somatic disorders in modern societies. Thus, there is substantial evidence showing that chronic stress can increase the likelihood of major depressive disorder and anxiety disorders, as well as cardiovascular diseases, irritable bowel syndrome and pain syndromes, to name but a few, in vulnerable individuals. Although a number of pharmacological agents are available to treat such stress-related disorders, many patients do not respond to them, and those who do often report a number of side effects. Therefore, a major emphasis in modern basic research is to uncover the underlying aetiology of these disorders, and to develop novel efficacious treatment strategies. This has led to a resurgence in developing, and using, appropriate animal models to study a wide variety of stress-related disorders. Thus, the aim of this research topic "Using stress-based animal models to understand the mechanisms underlying psychiatric and somatic disorders" was to bring together novel research articles and comprehensive review articles from prominent stress researchers. In addition to describing the insights such models have provided relating to the aetiology of psychiatric and somatic disorders, these articles also encompass mechanisms that are believed to underlie stress resilience and stress-protection. Finally, given the current prominence on the role of the brain-gut axis in health and disease, the research topic covers the emerging evidence showing how the gut, particularly the microbiota, influences affective behaviour and physiology.